2018
DOI: 10.1108/jrim-01-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

Home sweet virtual home

Abstract: Purpose Digital technologies have made it possible for organizations to enhance service delivery and provide consumers a way to experience a product or service before even seeing it in person. Prior work has validated consumer purchase decision-making models like the Engel, Kollat and Blackwell (EKB) model in digital and multi-channel purchase environments. This research aims to explore the various impacts of digital technologies, specifically virtual reality (VR) and augmented reality (AR) features, on the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 25 publications
3
19
0
4
Order By: Relevance
“…The potentials of digital visualisation for marketing research have also spanned across the residential real estate industry. Leading residential real estate companies in the United States, SASBE 11,4 such as Redfin and Sotheby's, have been utilising the VR technology for virtual tours, which allow users to be immersed in the simulated space and experience the house via 3D virtual walkthroughs (Sihi, 2018). Recent study has shown that VR and AR have a positive impact on the homebuying process, where it has been shown to provide both the homebuyers and the realtors great convenience in time, for example, by allowing homebuyers to experience homes in different geographical locations conveniently (Sihi, 2018).…”
Section: Vr In the Real Estate Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…The potentials of digital visualisation for marketing research have also spanned across the residential real estate industry. Leading residential real estate companies in the United States, SASBE 11,4 such as Redfin and Sotheby's, have been utilising the VR technology for virtual tours, which allow users to be immersed in the simulated space and experience the house via 3D virtual walkthroughs (Sihi, 2018). Recent study has shown that VR and AR have a positive impact on the homebuying process, where it has been shown to provide both the homebuyers and the realtors great convenience in time, for example, by allowing homebuyers to experience homes in different geographical locations conveniently (Sihi, 2018).…”
Section: Vr In the Real Estate Industrymentioning
confidence: 99%
“…However, there is a lack of study conducted to understand the impact of this technology on house purchase intention, compared with conventional marketing method using physically constructed show houses. Although VR technology for real estate is well accepted in the United States (Sihi, 2018), different cultural background could have an impact on the acceptance of this technology for house purchase. Thus, this paper aims to focus on potential homebuyers' emotions, satisfaction and intention to purchase a house in VR, specifically among Malaysian homebuyers.…”
Section: Vr In the Real Estate Industrymentioning
confidence: 99%
“…Tema ini muncul pada penelitian yang ditulis oleh Sihi (2018). Ia menyampaikan bahwa melalui penggunaan AR, seorang pelanggan real estate dapat menentukan pola lantai yang akan dibangun ataupun produk furniture yang akan dibeli.…”
Section: Kustomisasi Produkunclassified
“…Hal ini merusak konsep dasar komunikasi karena banyaknya distorsi yang menghalangi suatu pesan untuk diterima secara utuh oleh pengguna. Sihi (2018) menyampaikan bahwa pada konteks pemasaran produk real estate, teknologi AR harus mampu dibuat serealistis mungkin seperti aslinya sehingga semakin tinggi niatan pelanggan untuk membeli. Sihi mengatakan bahwa banyak pelanggan real estate yang berhenti menggunakan teknologi AR karena fitur dan visualisasinya tidak realistis.…”
Section: Tingginya Tingkat Kesulitan Dalam Membuat Konten Arunclassified
See 1 more Smart Citation